The rewind eaudiobook - Scotch, Allison Winn (Penguin Audio, 2022)
A Good Morning America Buzz Pick One of Amazon's Best Romances of November! Two exes wake up together with wedding bands on their fingers—and no idea how they got there. They have just one New Year’s Eve at the end of 1999 to figure it out in this big-hearted and nostalgic rom-com from New York Times bestselling author Allison Winn Scotch. When college sweethearts Frankie and Ezra broke up before graduation , they vowed to never speak to each other again. Ten years later, on the eve of the new millennium, they find themselves back on their snowy, picturesque New England campus together for the first time for the wedding of mutual friends. Frankie’s on the rise as a music manager for the hottest bands of the late ’90s, and Ezra’s ready to propose to his girlfriend after the wedding. Everything is going to plan—they just have to avoid the chasm of emotions brought up when they inevitably come face to face.   But when they wake up in bed next to each other the following morning with Ezra’s grandmother’s diamond on Frankie’s finger, they have zero memory of how they got there—or about any of the events that transpired the night before. Now Frankie and Ezra have to put aside old grievances in order to figure out what happened, what didn’t happen...and to ask themselves the most troubling question of all: what if they both got it wrong the first time around?